The empowering path: exploring the mediating role of entrepreneurship in the relationship between financial management skills, group identity, and women's empowerment in rural areas / Suhailah Kassim - Kassim, Suhailah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
Entrepreneurship mediates how financial management skills and group identification affect rural women's empowerment in this conceptual study. Women's empowerment is crucial to rural communities social and economic prosperity. This study links financial management, group identity, entrepreneurship, and rural women's empowerment. Financial management skills help women manage money, make wise business decisions, and prosper. Rural women feel supported and empowered by group identification. Entrepreneurship empowers women, according to the framework. This conceptual study integrates financial management skills, group identification, entrepreneurship, and rural women's empowerment into the literature. These links need empirical investigation to empower women and enhance rural socioeconomic development.